Academic Coaching Based Supervision for Strengthening Teachers’ Professional Competence in the Era of Educational Transformation: A Case Study in Primary School - Dian Putri Amelia; Soedjono Soedjono (Journal of Educational Sciences, 2026)
Educational transformation requires teachers to continuously develop professional competence to create adaptive, innovative, and student centered learning. Academic supervision should therefore function not only as an evaluation mechanism but also as a professional development strategy. However, conventional supervision often emphasizes administrative assessment rather than sustainable teacher improvement. This study aims to analyze the implementation of coaching-based academic supervision and its contribution to strengthening teachers’ professional competence at SD Negeri Balerejo. This study employed a qualitative approach with a case study design. Data were collected through interviews, classroom observations, and documentation involving the principal and teachers. Data were analyzed through data condensation, data display, and conclusion drawing, with credibility ensured through source and technique triangulation. The novelty of this study lies in explaining how coaching based academic supervision integrates instructional leadership, reflective dialogue, and continuous mentoring within a primary school context. The findings reveal that coaching based academic supervision improves teachers’ competence in developing instructional materials, implementing student centered learning strategies, utilizing educational technology, and conducting professional reflection. This study contributes to the development of academic supervision models by positioning supervision as a collaborative professional learning process rather than merely an evaluation activity.